A multilevel converter with a floating bridge for open-ended winding motor drive application - Chowdhury, MD Shajjad (2017)
In this thesis, a dual inverter topology is considered as an alternative to a multilevel converter for the control of high speed machines. Instead of feeding to one end of the stator with a single power converter, this topology feeds from both sides of the stator winding using two converters, thus achieving multilevel output voltage waveforms across the load. A large amount of published work in the area of open end winding power converter topologies are focused on symmetrical voltage sources. This published research recognises the advantages of the converter system in terms of increased reliability, improved power sharing capability and elimination of common mode voltages when compared to traditional single sided three phase converter solutions. However isolated DC supplies come with the price of additional components thus increase size, weight and losses of the converter system.